(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Blended learning has increasingly been recognized as an effectiveinstructional model in higher education, as it strategically integrates online digital resources with traditional face-to-face instruction to enhance the overall quality of teaching and learning. This pedagogical approach addresses the growing demand for flexible, learner-centered, and technology-enhanced educational environments. The present study investigates the effectiveness of blended learning models in integrating online and in-person instructional components and examines their influence on student engagement, learning outcomes, and instructional quality within higher education contexts. Employing amixed-methods research design, the study draws on data collected through classroom observations, student surveys, and analyses of academic performance. The findings reveal that blended learning significantly enhances student engagement, fosters autonomous and self-regulated learning, and improves knowledge retention compared to exclusively traditional instructional models. At the same time, the results indicate that the successful implementation of blended learning depends largely on the quality of instructional design, the level of digital literacy among instructors and students, and the availability of institutional support mechanisms. The study concludes that blended learning constitutes a sustainable and adaptable pedagogical model capable of effectively bridging traditional and digital forms of education, thereby offering valuable practical implications for higher education institutions seeking to modernize and optimize their teaching practices.